Commercial Diplomacy and business forums for stakeholder collaboration in South Africa : The Kimberley Process Certification Scheme - Graham, Victoria (University of Pretoria, 2022)
Mini Dissertation (MA (Diplomatic Studies))--University of Pretoria, 2021.